(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To investigate the antibiotic resistance patterns of Escherichia coli strains isolated from bloodstream infections at Hai Duong General Hospital in 2023. Methods: A cross-sectional study was conducted using medical records of patients who underwent blood culture testing at Hai Duong General Hospital from January to December 2023. Only the first E.coli isolate from each patient’s blood culture was included in the analysis. Antimicrobial susceptibility testing was performed using the disk diffusion method and interpreted according to CLSI (2023) guidelines. Results: Among 3436 blood culture samples, 149 E.coli isolates (3.4%) were identified. The proportion of E.coli isolates was higher in females (60.4%), predominantly in patients aged ≥ 60 years (72.5%), and mainly distributed in internal medicine departments (77.9%). E.coli showed low susceptibility to Penicillins, Cephalosporins, and Quinolones, with 72 ESBL-producing strains identified, while high susceptibility was observed to Aminoglycosides (Netilmicin 86.2%; Amikacin 85.3%) and Carbapenems (Meropenem 96.6%). Conclusions: E.coli is a major pathogen causing bloodstream infections and exhibits high resistance to commonly used antibiotics. Carbapenems and Aminoglycosides remain highly effective treatment options.